Curriculum Connections: Linking Literature and Math - Michelle Pasko (Networks: An Online Journal for Teacher Research, 2004)
I feel that math should be an enjoyable, not a tedious and boring, experience for students. One way to achieve this in a classroom is to make math meaningful and hands-on. Another useful strategy in teaching math is the use of math-related literature. Knowing that students love being read to, I have utilized storybooks in my math lessons in order to increase motivation and interest. Recognizing the importance of integrating subject matter in order to increase understanding, I set out on an adventure to research the following question: What kinds of mathematical connections can and do students make to literature?